Experimental study of rock permeability in different fluid media: a case study of two clay-free sandstones - Yang, Xin; Kang, Bo; Xu, Bin; Wang, Hehua; Zhou, Chunxiang; Jiang, Kai; Li, Xingfu (Frontiers in Earth Science, 2025)
Permeability is a fundamental property of porous media that governs the ability of a pore network to facilitate fluid flow through its pore spaces. However, the permeability test results are highly influenced by the type of fluid used during the measurements. This study investigates the influence of different fluids on permeability, excluding fluid-solid interactions. Permeability measurements were conducted on 30 clay-free Fontainebleau sandstones and 30 clay-free Y sandstones using kerosene and N2, with Klinkenberg-corrected gas permeability determined for comparison. Scanning electron microscopy (SEM) was employed to examine the presence of liquid films and particle migration within pore throats. The results consistently showed lower oil permeability compared to gas permeability across all samples. SEM analysis revealed that liquid films on rock surfaces and particle migration within pore throats contributed to the permeability disparity between liquid and gas in Fontainebleau sandstone. In contrast, the lower hydrophilicity of Y sandstone resulted in a negligible presence of liquid films, with particle migration being the primary factor for reduced liquid permeability. Furthermore, a more pronounced slip effect was observed in Y sandstone compared to Fontainebleau sandstone, attributed to its finer pore throats. These findings underscore the critical roles of liquid films, particle migration, and pore throat characteristics in determining permeability and highlight the relationship between the slip factor and permeability in porous media.